Modeling fuels and fire effects in 3D: Model description and applications. (June 2016) - Pimont, François; Parsons, Russell; Rigolot, Eric; de Coligny, François; Dupuy, Jean-Luc; Dreyfus, Philippe; Linn, Rodman R.
Abstract: Scientists and managers critically need ways to assess how fuel treatments alter fire behavior, yet few tools currently exist for this purpose. We present a spatially-explicit-fuel-modeling system, FuelManager, which models fuels, vegetation growth, fire behavior (using a physics-based model, FIRETEC), and fire effects. FuelManager's flexible approach facilitates modeling fuels across a wide range of detail. Large trees or shrubs with specific coordinates are modeled as individual " Plants ", while understory plants are modeled as collections of plants called " LayerSets ". Both Plants and LayerSets contain various fuel particles (leaves, needles, twigs) with various properties including shape, size and surface area to volume ratio. A wide range of vegetation and treatments can be modeled, analyzed quantitatively and visualized in a 3D viewer. We describe the modeling approach and demonstrate fuel modeling at different levels of detail, fuel treatment and fire effects capabilities. Detailed model equations are provided in the Appendices. Graphical abstract: Highlights: Comprehensive description of fuel modeling for a physics-based fire model. Different fuel items can be defined to model trees and plant collections. Fuel treatment, growth and fire effects can be simulated. Several applications of the model are demonstrated.